PHP in Action : objects, design, agility - Reiersøl, Dagfinn (Manning, 2007)
To keep programming productive and enjoyable, state-of-the-art practices and principles are essential. Object-oriented programming and design help manage complexity by keeping components cleanly separated. Unit testing helps prevent endless, exhausting debugging sessions. Refactoring keeps code supple and readable. PHP offers all this-and more. This book shows you how to apply PHP techniques and principles to all the most common challenges of web programming, including: Web presentation and templates User interaction including the Model-View-Contoller architecture Input validation and form handling Database connection and querying and abstraction Object persistence.